PERAN KADER JUMANTIK TERHADAP PERILAKU MASYARAKAT DALAM UPAYA PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) - Putri Abhen Chania; Zahrah Maulidia Septimar (Nusantara Hasana Journal, 2022)
Dengue Hemorrhagic Fever (DHF) is a health problem that must be watched out for in Indonesia. Transmitted by the Aedes sp. Especially Aedes aegypti to someone with another person, causing dengue hemorrhagic fever (DHF) is referred to as an infectious disease. This transmission is also influenced by the environment, such as a densely populated environment due to unplanned urbanization or an unsanitary environment, causing waterlogging. Thus, this can increase the risk of dengue hemorrhagic fever (DHF). Objective to find out the role of jumantik cadres on community behavior in efforts to prevent dengue hemorrhagic fever (DHF) in the Bugel Mas Indah Housing Area RW.009 in 2022. The design in this study used a cross sectional approach. Samples were taken using the Slovin formula with a total sample of 294 respondents. Sampling using simple random sampling technique. This study uses univariate analysis and bivariate analysis using Chi Square test. Based on the univariate analysis of 294 respondents, most of the jumantics played a significant role with the results of 168 respondents (57.1%) and the community had enough behavior to prevent DHF with the results of 210 respondents (71.4%). Bivariate results with Chi Square test obtained p-value 0.001 so it can be concluded that there is a relationship between the role of jumantik cadres and community behavior. It was found that there was a relationship between the role of jumantik cadres and the behavior of the community in the Bugel Mas Indah Housing Area RW.009.